Thematic characteristics of the modern vocabulary of state correspondence in the Russian language - Hussein Samir Addai; Methaq M. Ismail (مجلة الآداب, 2023)
The official vocabulary of Russian state correspondence is characterized by a high level of saturation with diplomatic terminology and terminology of international law, as well as standardized speech turns.